2020
DOI: 10.1128/aac.01001-20
|View full text |Cite
|
Sign up to set email alerts
|

First Report of Candidemia Clonal Outbreak Caused by Emerging Fluconazole-Resistant Candida parapsilosis Isolates Harboring Y132F and/or Y132F+K143R in Turkey

Abstract: Clonal outbreak of fluconazole-resistant (FLZR) Candida parapsilosis isolates have been reported in several countries. Despite being the second leading cause of candidemia, the azole resistance mechanisms and the clonal expansion of FLZR C. parapsilosis blood isolates have not been reported in Turkey. Herein, we consecutively collected the C. parapsilosis blood isolates (n=225) from the fifth largest hospital in Turkey (2007–2019), assessed their azole susceptibility pattern using CLSI M27-A3/S4, and sequenced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
123
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 71 publications
(139 citation statements)
references
References 44 publications
11
123
5
Order By: Relevance
“…A recent study explored antifungal susceptibility patterns of Candida bloodstream isolates in Turkey (1997–2017) and reported the lack of drug resistance for C. tropicalis ( Arikan-Akdagli et al, 2019 ). However, our single- and multi-center investigations conducted later in Turkey have revealed a very recent (from 2017 onward) emergence of azole/echinocandin-resistant and even MDR Candida species ( Arastehfar et al, 2020b,c , e ), suggesting the existence of the same trend for C. tropicalis . Therefore, we conducted a comprehensive multi-center study to update the rate of antifungal resistance among C. tropicalis blood isolates recovered in 2017–2019 in Turkey; some isolates recovered before 2017 but not analyzed in the previous study ( Arikan-Akdagli et al, 2019 ) were also included.…”
Section: Introductionmentioning
confidence: 84%
“…A recent study explored antifungal susceptibility patterns of Candida bloodstream isolates in Turkey (1997–2017) and reported the lack of drug resistance for C. tropicalis ( Arikan-Akdagli et al, 2019 ). However, our single- and multi-center investigations conducted later in Turkey have revealed a very recent (from 2017 onward) emergence of azole/echinocandin-resistant and even MDR Candida species ( Arastehfar et al, 2020b,c , e ), suggesting the existence of the same trend for C. tropicalis . Therefore, we conducted a comprehensive multi-center study to update the rate of antifungal resistance among C. tropicalis blood isolates recovered in 2017–2019 in Turkey; some isolates recovered before 2017 but not analyzed in the previous study ( Arikan-Akdagli et al, 2019 ) were also included.…”
Section: Introductionmentioning
confidence: 84%
“…Unfortunately, this wave of FLZR C. parapsilosis isolates has also been observed in Kuwait [166], USA [165,185], Brazil [167,168], South Korea [164], India [169], South Africa [182] and Turkey [170]. The high rate of FLZR for a species that used to be susceptible to azoles may have arisen from the disproportionate use of azoles in the hospital [170,182]. The notable increase in the prevalence of FLZR C. parapsilosis isolates could be a major threat in developing countries, in which the vast majority of candidemia cases are treated with FLZ [138,169,182,186].…”
Section: Candida Parapsilosismentioning
confidence: 99%
“…Furthermore, a Korean single-center study reported a significant increase in the prevalence of FLZR among 2015-2016 isolates when compared to 2011-2015 isolates (14.3% vs. 0.9%, respectively) [184]. Unfortunately, this wave of FLZR C. parapsilosis isolates has also been observed in Kuwait [166], USA [165,185], Brazil [167,168], South Korea [164], India [169], South Africa [182] and Turkey [170]. The high rate of FLZR for a species that used to be susceptible to azoles may have arisen from the disproportionate use of azoles in the hospital [170,182].…”
Section: Candida Parapsilosismentioning
confidence: 99%
See 2 more Smart Citations